Model Manajemen BUMDes Makmur Abadi Berbasis Pertanian di Desa Dulohupa Kecamatan Wonosari - Fibriyanti S. Lakoro (Yayasan Literasi Sains Indonesia, 2022)
Village-Owned Enterprises (BUMDes) are one of the instruments that manage local economic empowerment with various types of potential in developing businesses in the village. BUMDes as a commercial institution that has a goal or is oriented towards profit or profit through the sale of beneficial goods and services to the community. The type of research used is descriptive research with a qualitative approach. The data analysis method used is the Miles and Huberman model, namely data reduction, data presentation and conclusion drawing or verification. The results of the research and discussion are that success can be shown in BUMDes Makmur Abadi to achieve its business functions by meeting the needs and satisfaction of farmers, gaining profits and getting better benefits for the Government and the community in Dulohupa Village. Management model Dulohupa Village, but there needs to be another model that is able to support the business being run, such as a sustainable order to be able to obtain BUMDes organizational activities that provide more successful implementation of BUMDes Makmur at the appropriate stage so as to maximize profits and give more hope to the government and the goals of BUMDes Makmur Abadi can be achieved.